Mass spectrometry-based metabolic signatures of sex steroids in breast cancer - Choi, Man Ho (ELSEVIER IRELAND LTD, 2018)
Owing to controversy over the effects of steroids on breast cancer pathophysiology, comprehensive quantification of steroid hormones has been extensively considered in both clinical practice and biomarker discovery studies. In contrast to the traditional immunoaffinity-based assays, which show cross-reactivity and have poor validity at low levels of sex steroids, mass spectrometry is becoming a promising tool for measuring steroid levels in complex biological specimens. The Endocrine Society has announced and continuously updated on technical advances to apply high-quality breakthroughs in the clinical sciences. To avoid incorrect estimation of the steroids of interest, however, further emphasis should be made on the efficient separation by chromatography, such as gas and liquid chromatography, prior to mass spectrometric (MS) detection. Recent advances in MS-based analysis of sex steroids associated with breast cancer enable accurate quantification of circulating as well as localized steroids from frozen tissue slices, allowing these assays to be more powerful in clinical practice. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: POSTMENOPAUSAL WOMEN; CHROMATOGRAPHY/MASS SPECTROMETRY; ESTROGEN-LEVELS; LC-MS/MS; PREMENOPAUSAL WOMEN; REFERENCE INTERVALS; SERUM ESTROGENS; HUMAN PLASMA; ESTRADIOL; HORMONES